My T. Vu. World population projections 1985 : short -and long- term estimates by age and sex with related demographic statistics. Baltimore ; Londres : The World Bank and the Johns Hopkins University Press, 1985 - Partida Bush, Virgilio (Estudios Demográficos y Urbanos, 1987)
MY T. VU. World Population Projections 1985. Short —and Long—Term Estimates by Age and Sex with Related Demographic Statistics, The World Bank and The Johns Hopkins University Press, Baltimore y Londres, 1985.